Diversity of dragonflies (Odonata) as bioindicators of water quality in Mangkol river, Terak village, Simpang Katis subdistrict, Central Bangka regency - Zunnikah, Zunnikah; Hadisusanto, Suwarno; Nurjani, Emilya (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
Dragonflies (Odonata) can serve as bioindicators of environmental quality, especially water quality. The Mangkol River, located within Bukit Mangkol Grand Forest Park (Tahura), Terak Village, Central Bangka Regency, is a raw water source used by residents of Pangkalpinang City through the regional water company, Perumda Air Minum Tirta Pinang. While the river’s upstream serves as a raw water source, illegal tin mining activities in the midstream and downstream sections have altered the river's condition, causing sedimentation and turbidity. This study aimed to examine dragonfly diversity as bioindicators of water quality in the Mangkol River. Dragonflies were observed using the cruising method and direct capture with insect nets, supplemented with water quality data measured in the field and laboratory. Dragonfly diversity comprised 2 families, 12 species, and a total of 104 individuals. The Family Biotic Index (FBI) indicated poor water quality at station 1 (6.90) and very poor quality at stations 2, 3, and 4 (9.00).